The prevalence of natural tooth colors in the people of North India - Harinder Kuckreja; K B S. Kuckreja; Dalbir Bhullar; Sangeeta Nahar; Aakriti Singh; Aditi Jain (Wolters Kluwer Medknow Publications, 2017)
Aims and Objectives: Tooth color is a major factor with regard to dental esthetics. Restorative dentistry has evolved from its previous dentist driven to patient driven service and patient opinion plays an important role in selecting the treatment plan. Whitening teeth and smile designing for esthetic purpose is currently fashionable. Selection of appropriate tooth shade for edentulous patients is an important part of teeth replacement. Most patients prefer having lighter shades. However ultimate objective of esthetic dentistry is to create a beautiful smile, with teeth of pleasing inherent proportions to one another and color in harmony with gingiva, lips and face of the patient. Proper shade selection has a positive impact on the patient's acceptance of the treatment. The present study was designed to measure the tooth colors in a particular age group of North Indian population. There is enough data to support the use of objective methods of measuring shade and dentists are shifting to these newer technologies but subjective methods of shade selection are still popular as the digital devices are expensive. Materials and Methods: In the present study, shade of cervical, middle and incisal third of the facial surface of natural maxillary central incisor was measured with digital colorimeter, VITA Easyshade® Advance 4.0. It is an optical reading device that can assess the wavelengths reflected back to its sensors. Lighting in operatory does not affect the shade measurement. It is extremely accurate. The limitation of study was its small sample size. Conclusion: It was concluded that the most prevalent shade in cervical third was 1M2, middle third was 1M1 and incisal third was 2M1.